Prescription of psychotropic medication in patients with type two diabetes mellitus: A multi-practice study from Ireland. (3rd July 2019) - Keating, Paul; O'Connor, Ray; O'Doherty, Jane; Hannigan, Ailish; Cullen, Walter; Hickey, Louise; Harnett, Anne; Meagher, David; O'Regan, Andrew
Abstract: Background: Comorbid anxiety and depression and type two diabetes mellitus (T2DM) are commonly managed by General Practitioners (GPs). Objectives : To investigate the proportion of people with T2DM who are prescribed either antidepressant or benzodiazepine medications in general practice; to compare people with T2DM that have a prescription with those that do not in terms of patient characteristics, glycaemic control and healthcare utilization. Methods : Anonymized data was collected by GPs and senior medical students from electronic medical records of patients with T2DM in 34 Irish general practices affiliated with the University of Limerick Graduate Entry Medical School during the 2013/14 academic year. Data included demographics, healthcare utilization, prescriptions and most recent glycosylated haemoglobin (HbA1c) measurement. Results : The sample included 2696 patients with T2DM, of which 733 (36.7%) were female, and with a median age of 66 years. The percentage with a current prescription for an antidepressant or benzodiazepine was 22% (95%CI: 18.9–24.9). Those with a current prescription for either drug were more likely to have attended the emergency department (28.3% vs 15.7%, P <0.001), to have been admitted to hospital (35.4% vs 21.3%, P <0.001) in the past year and attend their GP more frequently (median of 9 vs 7, P <0.001) than those without a prescription. Rates of poor glycaemic control were similar in those with and without a current prescription. Conclusion : Over one-fifth of people with T2DM in Irish general practice are prescribed an antidepressant or benzodiazepine medication. Prescription of these is associated with increased healthcare utilization but not poorer glycaemic control.